Monetary Policy and Currency Stability Analyzing the Impact of Policy Tools and External Factors in Developing Countries - Nurhaliza, Nurhaliza; Gafur, Ahmad; Nugroho, Agung (Scieclouds Publishing, 2024)
This paper aims at reviewing the effect of the monetary policy towards currency stability in developing countries with reference to the manner in which monetary instruments and external shocks affect the exchange rate and inflation rates. The analysed data concerns several developing countries for the period 2010-2020, and applied methodology involves both regression and sensitivity analysis. Major conclusions show that both the interest rates and the inflation rates rise, lead to increase in exchange rates volatility, but the reserve requirements and the foreign reserves have a positive effect on the exchange rates stability. Advanced analyses endorse that the external factor like as external debt and commodity exports have a crucial influence on the currency stability. Also, it analyses implications of the non-standard measures like quantitative easing, and establish that currency debasement may have dangers for emerging market economies with balance of payment risks. With this research, the following gaps in the existing literature are covered: First, it presents a more profound perspective on the effectiveness of monetary policy and second, it contributes an understanding of the relationship of monetary policy and the stability of its currency. The implications of the findings are therefore as follows Policies for developing countries have been reviewed and it has been made very clear that monetary policies should be undertaken cautiously in order to reduce on inflation as well as external factors affecting the economy.